2018
DOI: 10.7759/cureus.2632
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus Agalactiae Infective Endocarditis in a Healthy Middle-aged Man: Uncommon but Life-threatening

Abstract: Streptococcus agalactiae (S.agalactiae) is known to cause invasive infections in pregnant women, newborns, and immunosuppressed patients. It is an uncommon but life-threatening case of infective endocarditis in middle-aged otherwise healthy adults. We present a case of a patient with life-threatening infective endocaritis caused by Streptococcus agalactiae, who passed away despite medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is worth noting that most species identified in this study are typically found in soil, seawater, sediments, and human skin or gut microbiota, and only a few species have been recently reported in the literature to cause rare infections in people, such as Corynebacterium sanguinis (Jaen-Luchoro et al, 2020), Dermabacter jinjuensis (Cho et al, 2018), Dermacoccus nishinomiyaensis (Joron et al, 2019;Ogbac, 2021), Enterococcus faecalis (Li et al, 2020), Rhodococcus corynebacterioides (Kitamura et al, 2012), Brachybacterium paraconglomeratum (Murata et al, 2020), Streptococcus agalactiae (Yaqoub et al, 2018), Micrococcus luteus (Zhu et al, 2021) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017;Jeon et al, 2022;Muraki et al, 2022, Uddin et al, 2022Vasconcellos et al, 2022).…”
Section: Air Sampling Protocols and Bacterial Identificationmentioning
confidence: 85%
“…It is worth noting that most species identified in this study are typically found in soil, seawater, sediments, and human skin or gut microbiota, and only a few species have been recently reported in the literature to cause rare infections in people, such as Corynebacterium sanguinis (Jaen-Luchoro et al, 2020), Dermabacter jinjuensis (Cho et al, 2018), Dermacoccus nishinomiyaensis (Joron et al, 2019;Ogbac, 2021), Enterococcus faecalis (Li et al, 2020), Rhodococcus corynebacterioides (Kitamura et al, 2012), Brachybacterium paraconglomeratum (Murata et al, 2020), Streptococcus agalactiae (Yaqoub et al, 2018), Micrococcus luteus (Zhu et al, 2021) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017;Jeon et al, 2022;Muraki et al, 2022, Uddin et al, 2022Vasconcellos et al, 2022).…”
Section: Air Sampling Protocols and Bacterial Identificationmentioning
confidence: 85%
“…It is worth noting that most species identified in this study are typically found in soil, seawater, sediments, and human skin or gut microbiota, and only a few species have been recently reported in the literature to cause rare infections in people, such as Corynebacterium sanguinis (Jaén‐Luchoro et al, 2020 ), Dermabacter jinjuensis (Cho et al, 2018 ), Dermacoccus nishinomiyaensis (Joron et al, 2019 ; Ogbac, 2021 ), Enterococcus faecalis (Li et al, 2020 ), Rhodococcus corynebacterioides (Kitamura et al, 2012 ), Brachybacterium paraconglomeratum (Murata et al, 2020 ), Streptococcus agalactiae (Ya'qoub et al, 2018 ), Micrococcus luteus (Zhu et al, 2021 ) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017 ; Jeon et al, 2022 ; Muraki et al, 2022 ; Uddin et al, 2022 ; Vasconcellos et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dermabacter jinjuensis (Cho et al, 2018), Dermacoccus nishinomiyaensis (Joron et al, 2019;Ogbac, 2021), Enterococcus faecalis (Li et al, 2020), Rhodococcus corynebacterioides (Kitamura et al, 2012), Brachybacterium paraconglomeratum (Murata et al, 2020), Streptococcus agalactiae (Ya'qoub et al, 2018), Micrococcus luteus (Zhu et al, 2021) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017;Jeon et al, 2022;Muraki et al, 2022;Uddin et al, 2022;Vasconcellos et al, 2022).…”
Section: Air Sampling Protocols and Bacterial Identificationmentioning
confidence: 99%